China Wildfire Emission Dataset (ChinaWED v1) for the period 2012–2022 - Z. Lin; L. Huang; H. Tian; H. Tian; A. Chen; X. Wang (Geoscientific Model Development)
During the past decades, wildfires have undergone rapid changes while both the extent of fire activities and the resulting greenhouse gas (GHG) emissions from wildfires in China have remained inadequately quantified. We established a wildfire emission model to generate the China Wildfire Emission Dataset (ChinaWED), which can be used to explore the recent dynamics at a national scale. This dataset is constructed at a monthly and kilometer scale under a consistent and quantifiable calculation framework, providing average annual estimates of wildfire-induced GHG emissions of 78.13 ± 22.46 Tg CO2, 279.47 ± 82.01 Gg CH4, and 6.26 ± 1.67 Gg N2O (Tg denotes teragrams and Gg gigagrams) for the past decade. We observed significant decreases in both wildfire occurrences and emissions within forests and grasslands. This trend, however, is counteracted by variations in agricultural fires, which constitute the primary type of fire, accounting for at least half of the national total fire emissions. The seasonal cycle of wildfire GHG emissions shows an evident apex that occurs during the transition from mid-spring to early summer. At the regional scale, northeast China, southwest China, and east China emerge as hotspots of wildfire-induced emissions. Our study offers new insights into China's wildfire dynamics and provides a detailed regional model for wildfire greenhouse gas emissions over China.